Bilateral Optic Neuritis after COVID-19 mRNA Vaccination - Hiroyasu Katayama; Kaku Itoh; Masato Hashimoto (Case Reports in Ophthalmology, 2022)
We report the case of a healthy man who was diagnosed with bilateral optic neuritis after COVID-19 vaccination. A 63-year-old man presented with acute painful blurred vision in his left eye and temporal pain. Eleven days before the appearance of his symptoms, he received the first dose of COVID-19 mRNA vaccination. On examination, his best corrected visual acuity was 20/20 in his right eye and counting fingers in the left eye. Funduscopic examination showed bilateral optic disc swelling, and postcontrast magnetic resonance imaging showed left optic nerve sheath enhancement, consistent with left optic perineuritis and right optic papillitis. After steroid pulse therapy, his visual function and headache showed significant improvement. A few cases of optic neuritis as a side effect of COVID-19 mRNA vaccination were reported. This report provides important information about side effects assumed to be related to the COVID-19 mRNA vaccine.